Maheshwari handloom weaving tradition : a living cultural heritage - Khare, Astha (Penerbit Universiti Kebangsaan Malaysia, 2019)
The handloom weaving tradition of India is an outstanding example of traditional craftsmanship. The heritage of weaving is not only limited to the traditional looms, craftsmanship or the sarees1, but also constitutes of the spaces in which weaving is practiced. The houses of craftsmen are examples of vernacular architecture, which has evolved over a large span of time. Maheshwar Tehsil2 in Madhya Pradesh, is one such outstanding example, where the centuries old weaving tradition has been revived by the Royal descendants. As the city is growing, the vernacular architecture is gradually transforming to modern style, disturbing the authenticity of the tradition as well as living comfort in the houses and workspaces. There lies great potential in this region which has not been documented and needs to be strengthened. This paper, with a qualitative as well as quantitative approach, is an attempt to establish the significance of Maheshwari Handloom weaving tradition as a living cultural heritage. The data collection has been done on two levels - primary as well as secondary, which was further followed by the analysis (including listing & grading) of heritage components. Weavers’ houses as well as the weaving techniques have been documented, along with the inventory mapping of the tehsil, and factors impacting the heritage are analyzed to propose appropriate conservation strategies to safeguard the vernacular methods in the contemporary time and style. It has been found out through the study that, the weaving tradition in Maheshwar is in its authentic form, but the various issues of the household handloom facilities and also of the unorganised and dispersed weaving clusters in the region are not addressed by the government while proposing various schemes and providing privileges to the bigger weaving societies. In addition, there is lack of education, adequate workingcapital, proper infrastructure, qwpoor exposure to new technologies, lack of market intelligence, stiff competition and poor institutional framework. Thus based on these findings, guidelines and recommendations have also been proposed.